PERILAKU MASYARAKAT SUNDA MUSLIM DALAM MENGONSUMSI PRODUK HALAL DI KOTA BANDUNG - Mulyaningrum Mulyaningrum; Erik Syawal Alghifari (Jurnal Riset Bisnis dan Manajemen, 2018)
This study aims to analyze the relationship between the level of knowledge and behavior of the Sundanese Muslim community in Bandung about halal food and beverage products. The method used in this research is descriptive and verifikatif. The data were collected using questionnaires, completed with observation. Data analysis using validity test, reliability test, linear regression, correlation, hypothesis test, and coefficient of determination. The correlation test result is 0.376, which shows that it is in the interval 0.20 - 0.399, and the coefficient of determination test shows the influence of 0.142. This means that the influence of knowledge level on the behavior of Muslim sunda society is 14.2%. The difference of 85.8% is the influence of other factors not examined. This figure indicates that the increased knowledge of respondents on halal products will increase the behavior in consuming halal products.